Effects of preventative ankle taping on planned change-of-direction and reactive agility performance and ankle muscle activity in basketballers - Jeffriess, M. D.; Schultz, A. B.; McGann, T. S.; Callaghan, S. J.; Lockie, R. G. (Journal of Sports Science & Medicine, 2015)
This study investigated the effects of preventative ankle taping on planned change-of-direction and reactive agility performance and peak ankle muscle activity in basketballers. Twenty male basketballers (age = 22.30 ± 3.97 years; height = 1.84 ± 0.09 meters; body mass = 85.96 ± 11.88 kilograms) with no ankle pathologies attended two testing sessions. Within each session, subjects completed six planned and six reactive randomized trials (three to the left and three to the right for each condition) of the Y-shaped agility test, which was recorded by timing lights. In one session, subjects had both ankles un-taped. In the other, both ankles were taped using a modified subtalar sling. Peak tibialis anterior, peroneus longus (PL), peroneus brevis (PB), and soleus muscle activity was recorded for both the inside and outside legs across stance phase during the directional change, which was normalized against 10-meter sprint muscle activity (nEMG). Both the inside and outside cut legs during the change-of-direction step were investigated. Repeated measures ANOVA determined performance time and nEMG differences between un-taped and taped conditions. There were no differences in planned change-of-direction or reactive agility times between the conditions. Inside cut leg PL nEMG decreased when taped for the planned left, reactive left, and reactive right cuts (p = 0.01). Outside leg PB and soleus nEMG increased during the taped planned left cut (p = 0.02). There were no other nEMG changes during the cuts with taping. Taping did not affect change-of-direction or agility performance. Inside leg PL activity was decreased, possibly due to the tape following the line of muscle action. This may reduce the kinetic demand for the PL during cuts. In conclusion, ankle taping did not significantly affect planned change-of-direction or reactive agility performance, and did not demonstrate large changes in activity of the muscle complex in healthy basketballers.